(untitled) (Research, Society and Development, 2020)
Aiming at the Italac Food quality standard, where its products are in more than twenty thousand points of sale in the country and for the benefit of the community in partnership with the university, the quality of the raw material that arrives directly from the producer in the industry was evaluated. The objective of this work was to analyze the microbiological quality of raw milk in 27 tanks between manual and mechanical milking in rural properties in the municipality of Rolim de Moura - RO. The samples were analyzed using the most likely number (NMP) method. The results revealed that 100% of the samples were positive for total coliforms and 60% for thermotolerant coliforms. With significant difference between the types of milking, where 50% of the mechanical milking samples were negative for E. coli, in the manual milking only 17.64% were negative, showing the need for greater quality control and guidance to the producer on best hygiene techniques.